2020
DOI: 10.1186/s12935-020-01509-z
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of TRIB3 inhibits the progression of ovarian cancer via MEK/ERK signaling pathway

Abstract: Background: Tribbles pseudokinase 3 (TRIB3) protein is a pseudokinase which plays an important role in cellular stress, metabolism, and tumor progression. However, the expression and function of TRIB3 in ovarian cancer is unknown. Methods: TRIB3 expression was detected by immunohistochemistry in the ovarian tissue samples. Following downregulation of TRIB3 by siRNA, multiple aspects of ovarian cancer cells were detected by the MTT assay, flow cytometry, scratch test and Transwell. Additionally, changes in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Western blotting was conducted in accordance with specific protocols. 21 In the present work, the primary antibodies utilized included anti-MMP9 (Proteintech, Cat# 10375-2-AP), anti-PCNA (CST, Cat# 2586S), anti-IBSP (CST, Cat# 5468S), anti-E-cadherin (CST, Cat# 3195T), anti-MMP2 (Proteintech, Cat# 10373-2-AP), anti-N-cadherin (CST, Cat#13116T), anti-Vimentin (CST, Cat# 5741S), anti-CyclinD1 (CST, Cat# 55506S), anti-Cdk4 (CST, Cat# 12790T), anti-Bcl-2 (CST, Cat# 15071T), anti-Bax (CST, Cat# 5023S), anti-Fyn (Abcam, Cat# ab125016), antip-Fyn (phosphor Y530, Abcam, Cat# ab188319), anti-βcatenin (CST, Cat# 8480T), anti-p-β-catenin (phosphor Y142, Abcam, Cat# ab27798), and anti-β-actin (Beyotime Bio Inc, Cat#AA128). Besides, the enhanced chemiluminescence (ECL) detection system was employed to detect the protein-antibody complex.…”
Section: Western Blottingmentioning
confidence: 99%
“…Western blotting was conducted in accordance with specific protocols. 21 In the present work, the primary antibodies utilized included anti-MMP9 (Proteintech, Cat# 10375-2-AP), anti-PCNA (CST, Cat# 2586S), anti-IBSP (CST, Cat# 5468S), anti-E-cadherin (CST, Cat# 3195T), anti-MMP2 (Proteintech, Cat# 10373-2-AP), anti-N-cadherin (CST, Cat#13116T), anti-Vimentin (CST, Cat# 5741S), anti-CyclinD1 (CST, Cat# 55506S), anti-Cdk4 (CST, Cat# 12790T), anti-Bcl-2 (CST, Cat# 15071T), anti-Bax (CST, Cat# 5023S), anti-Fyn (Abcam, Cat# ab125016), antip-Fyn (phosphor Y530, Abcam, Cat# ab188319), anti-βcatenin (CST, Cat# 8480T), anti-p-β-catenin (phosphor Y142, Abcam, Cat# ab27798), and anti-β-actin (Beyotime Bio Inc, Cat#AA128). Besides, the enhanced chemiluminescence (ECL) detection system was employed to detect the protein-antibody complex.…”
Section: Western Blottingmentioning
confidence: 99%
“…Flow cytometry analysis revealed that arrested G0/G1 cell cycle could be induced by TRIB3-siRNA, confirmed by statistical analysis (Figure 7D), thereby inhibiting the proliferation and migration of bladder cancer cells. Other studies confirmed that the expression of TRIB3 is greater in solid tumors such as colorectal cancer, breast cancer, lung cancer, ovarian cancer, melanoma, liver cancer, and leukemia (Wennemers et al, 2011;Salazar et al, 2015;Hua et al, 2019;Wang et al, 2020;Zhu et al, 2020), suggesting that TRIB3 is a potential target for cancer treatment. Some studies have shown that biological scaffold coordination complexes can be used to design new target-specific therapeutic agents, and TRIB3 is also a scaffold protein that acts as a platform response.…”
Section: Discussionmentioning
confidence: 83%
“…Studies confirmed that inhibition of the expression of TRIB3 in ovarian cancer cells causes cell cycle arrest in the G0/G1 phase in ovarian cancer cells. Proliferation, migration, and invasion of ovarian cancer cells reduce, and apoptosis increases ( Wang et al, 2020 ). Enrichment analysis of co-expressed genes of TRIB3 showed that TRIB3 was related to the cell cycle ( Figure 6A ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support a scenario in which the balance between the expression of Tribbles might determine tumor progression, in this particular case through FOXO proteins activity via AKT. Several studies have been published reporting the role of Tribbles proteins in different types of cancer, including TRIB1 in prostate [ 34 ], glioma [ 35 ], ovarian [ 36 ], and thyroid [ 37 ] cancers; TRIB2 in melanoma [ 38 ], lung [ 39 ], liver [ 40 , 41 , 42 ], acute leukemias [ 27 , 43 , 44 ], and glioblastoma [ 45 ]; and TRIB3 in lung [ 46 ], breast [ 47 , 48 ], renal [ 49 ], gastric [ 50 ], liver [ 51 ], retinoblastoma [ 52 ], glioblastoma [ 53 ], and ovarian [ 54 ] cancers; as well as all Tribbles members in colorectal cancer, as herein fully presented. Tribbles pseudokinases may have an immediate impact in cancer treatment being potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%